1ISG-016 Envisioning sustainability in personalised medicine: Fondo AIFA 5% and the Italian example. (24th March 2020) - Bocchio, F; Tizzoni, M; Calvi, M; Di Benedetto, A
Abstract : Background and importance: Sustainability in the era of personalised medicine represents one the major problems because of the possible limited access to innovative therapies. Since 2003, the Agenzia Italiana del Farmaco (AIFA), along with pharma industries, has established an innovative and unique programme, 'Fondo 5%', 1 to deliver innovative and highly expensive therapies to patients with rare diseases after their approval by the EMA but before AIFA authorisation and reimbursement for the specific indication. A joint evaluation by physicians and clinical pharmacists, based on the scientific literature, clinical reports, treatment plan and cost estimate analysis, produces a patient specific request for a peculiar drug not otherwise available through conventional channels. AIFA is responsible for the scientific evaluation, and final authorisation or rejection. Once the treatment plan has received AIFA official approval, the clinician is authorised to administer the therapy whose cost will be subsequently refunded by the AIFA. 2 Aim and objectives: To describe the Italian method in order to improve the availability of the best innovative therapies, considering sustainability of the national health system. Material and methods: Collection and processing of drug requests for Fondo 5% and analysis of the clinical and economic impact. Results: From August 2018 to September 2019, 24 treatments were authorised by AIFA: 20 (83%) in the adult and paediatric haematological area (venetoclax for acute myeloid leukaemia/mantle cell lymphoma, eltrombopag for pure red cell aplasia, pembrolizumab for Hodgkin lymphoma/non-Hodgkin lymphoma, ruxolitinib for myeloproliferative neoplasm BCR/JAK2-rearranged, blinatumomab for acute lymphoblastic leukaemia, ruxolitinib for graft versus host disease); 3 requests (12%) came from the oncological/gynaecological area (trabectedina for tube ovarian carcinoma and serous ovarian adenocarcinoma) and 1 (5%) from the ophthalmology area (cenegermin for neurotrophic keratitis). Eight of 24 authorised patients (33%) are still receiving treatment and 16 (67%) have completed their treatment programme. Of note, 16/23 (70%) oncologic patients had a disease response; moreover, 4/9 (44%) high risk acute leukaemia patients have undergone bone marrow transplant. The total cost of the authorised treatments was about € 700 000, of which €142 000 was already credited back to the hospital. Conclusion and relevance: These results demonstrate that Fondo 5% represents a scientific based method guaranteeing access to highly expensive therapeutic programmes, impacting on patient survival, without affecting the cost effectiveness balance and sustainability of the national health system. References and/or acknowledgements: 1. L.326/2003 2. www.aifa.gov.it/fondo-nazionale-aifa No conflict of interest.